Non-practising entities (NPEs) and patent remedies for future infringement - Park, Jae-il (2013)
This research establishes a new patent remedy (injunction) system against future infringements in such a way as to discourage trolling behaviours of non-practising entities (NPEs) without chilling inventors’ incentives to innovate. For this research target, this thesis reviewed the general characteristics of NPEs in the current and past patent system, the current patent remedy laws in different countries (the US, UK and Germany), the patent holdups caused by NPEs’ patent enforcement against manufacturers, and various solutions which have been proposed so far. In doing so, it addresses important findings that the major cause of NPE problems stems from the inherent uncertainty nature of patent, that the courts’ discretion of whether to grant or deny an injunction needs to be clearly defined, and that the new injunction system should skilfully balance the short-term as well as the long-term transaction costs which are caused by NPEs’ patent enforcements. Considering these findings, this thesis proposes a new injunction model, alias a ‘three-tiered remedy system.’ Unlike the present two-tiered system, it divides the remedies into three different types: (1) granting an unqualified injunction against wilful infringers; (2) granting a suspended injunction against innocent infringers; and (3) denying injunctions in exceptional circumstances. The most differentiated feature of this model is to award a suspended injunction as a default remedy in order to mitigate the patent holdup arising from the uncertainty problem of patent. Since the suspension period is determined in proportion to the required time for designing around the infringed patent, this new model can provide a very useful solution to mitigate the harmful effect of NPEs’ patent enforcement without jeopardizing the integrity of exclusive right of patent at the same time.